Performance of a Novel Low-Cost, Instrument-Free Plasma Separation Device for HIV Viral Load Quantification and Determination of Treatment Failure in People Living with HIV in Malaysia: a Diagnostic Accuracy Study - Pham, Minh D.; Haile, Berhan A.; Azwa, Iskandar; Kamarulzaman, Adeeba; Raman, Nishaan; Saeidi, Alireza; Abdul Kahar, Maria Kahar Bador; Tan, Margaret; Zhu, Jiawei; Feng, Yi; Elliott, Julian H.; Garcia, Mary L.; et al. (American Society for Microbiology, 2019)
HIV viral load (VL) testing is the recommended method for monitoring the response of people living with HIV and receiving antiretroviral therapy (ART). The availability of standard plasma VL testing in low- and middle-income countries (LMICs), and access to this testing, are limited by the need to use fresh plasma. Good specimen collection methods for HIV VL testing that are applicable to resource-constrained settings are needed. We assessed the diagnostic performance of the filtered dried plasma spot (FDPS), created using the newly developed, instrument-free VLPlasma device, in identifying treatment failure at a VL threshold of 1,000 copies/ml in fresh plasma. Performance was compared with that of the conventional dried blood spot (DBS). Venous blood samples from 201 people living with HIV and attending an infectious disease clinic in Malaysia were collected, and HIV VL was quantified using fresh plasma (the reference standard), FDPS, and DBS specimens. VL testing was done using the Roche Cobas AmpliPrep/Cobas TaqMan v2.0 assay. At a threshold of 1,000 copies/ml, the diagnostic performance of the FDPS was superior (sensitivity, 100% [95% confidence interval CI, 89.1 to 100%]; specificity, 100% [95% CI, 97.8 to 100%]) to that of the DBS (sensitivity, 100% [95% CI, 89.4 to 100%]; specificity, 36.8% [95% CI, 29.4 to 44.7%]) (P < 0.001). A stronger correlation was observed between the FDPS VL and the plasma VL (r = 0.94; P < 0.001) than between the DBS VL and the plasma VL (r = 0.85; P < 0.001). The mean difference in VL measures between the FDPS and plasma (plasma VL minus FDPS VL) was 0.127 log10 copies/ml (standard deviation [SD], 0.32), in contrast to -0.95 log10 copies/ml (SD, 0.84) between the DBS and plasma. HIV VL measurement using the FDPS outperformed that with the DBS in identifying treatment failure at a threshold of 1,000 copies/ml and compared well with the quantification of VL in plasma. The FDPS can be an attractive alternative to fresh plasma for improving access to HIV VL monitoring among people living with HIV on ART in LMICs. Copyright © 2019 Pham et al.